PENERAPAN ASAS RETROAKTIF DALAM PELANGGARAN HAK ASASI MANUSIA - Ramadani, Fitri; Halimang, St; Risal, Chaerul (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
This research aims to describe the application of the Retroactive Principle in Human Rights Violations. The assertion of human rights in Indonesia experiences a very definite dilemma in law enforcement considering the many past human rights violations that have not been resolved. Thus, this research uses a type of library research with a normative juridical approach and a syar'I approach. This data collection method involves studying several primary data sources extracted from scientific works, documents and relevant books. The research results show that the retroactive principle is a principle or legal principle that can be implemented in upholding human rights, with 4 cumulative conditions, namely: 1) The criminal act committed is a serious human rights violation; 2) the nature of justice must be international; 3) justice is ad-hoc; 4) the government's inability to prosecute crimes, both in terms of cruelty and damage.